Valorisation des terres salées par la culture Du Ricinus communis L. à Mostaganem - DJELLOUL DAOUADJI, ABDERRAHMANE; MOHAMED BENKOIBICH, ISMAIL (My University, 2023)
Salt lands represent a major environmental and agricultural and economical problem in the Mostaganem region of Algeria. Their high salt content makes growing plants difficult and leads to loss of soil fertility. Soil salinization in this region is mainly due to pedoclimatic factors. This study focuses on the adaptation of castor bean to saline soils in Mostaganem, which is of great importance to promote sustainable agriculture and preserve the country's natural resources. By studying the adaptability of castor bean to these saline soils, we first identified the presence of castor bean in different regions of Mostaganem and in the surrounding areas with soils considered saline. Then, we analyzed the samples taken from four types of soil by specifying the parameters of electrical conductivity, grain size and KCL pH ,The results showed that three types of soils, namely Light Stidia (177.5 μs/cm), Light Mactaa (71.6 μs/cm) and not very light Ain Sefra (132.8 μs/cm), were favorable to the development of the roots of the castor bean plant. In contrast, the heavy soil type Mactaa had high salinity (5.88 ms/cm) and was therefore unsuitable for agriculture. This study, carried out over a short period, constitutes a step forward in the reflection on the valuation of successful land as unsuitable for agriculture in Mostaganem.
Keywords: Salinity; Castor; Adaptation; Alka line